The Role of Preschool Male Teacher in Islamic Moral Education - Putri, Wiwit Purnama (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, 2023)
The phenomenon of male participation as preschool teachers turns out to have a positive impact in overcoming moral decline in early childhood. The form of this effort is to nurture Islamic moral education as early as possible. The purpose of this study was to find out the form and the supporting factors for the role of preschool male teachers in Islamic moral education. The research method is qualitative research with a phenomenological approach. The subjects of this study were a male teacher, two female teachers, and two children caretaker at TK Aisyiyah Bustanul Athfal 1 Ngawi. Data collection techniques used are observation, interviews, and documentation. The results of this study indicate that the role of preschool male teachers has a positive impact on inculcating Islamic morality in early childhood. The findings of this study are, the form of the role of preschool male teachers in Islamic moral education, namely, exemplary, habituation, and advice. Factors supporting the role of preschool male teachers in Islamic moral education, namely the presence of school programs and parental support.